Una visión sucinta de la enseñanza de la medicina a través de la historia : II. Colombia, un sitio donde confluyeron varias culturas con su arte de curar (2011)
ABSTRACT: In order to understand how medicine has been taught through the years, it is necessary to refer to historians who have approached the evolution of medicine. Taking them as a starting point, it is possible to describe the attitudes of doctors in their role as professors, and the ways in which students acquired knowledge at different moments throughout centuries. This article presents a succinct vision of the evolution of medical teaching in Colombia, starting with the arrival of the Spanish conquerors. Several ways of practicing and teaching medicine, the Spanish and the aboriginals, coexisted. The evolution of medical teaching in Colombian universities is succinctly described, as well as the current curricular proposal at the Faculty of Medicine, University of Antioquia.